CHILDREN WITH DISABILITIES AND THE CHALLENGES OF SOCIETAL TRANSFORMATIONS: A CASE STUDY OF A DEAF CHILD - Hadjera Boukernafa; Ismaa Bekkal (International Journal of Innovative Technologies in Social Science, 2025)
This study aimed to ascertain the reality of children with special needs (deaf children), particularly in light of developments occurring in all areas of life. It has therefore become necessary to accord attention and priority to this group by developing the methods and curricula of special education provided to them within a framework that ensures that they keep pace with current social transformations and technological advances in this field. From this premise, we seek to answer a central question:– How do social transformations affect children with special needs? Moreover, what challenges does special education face in this regard?